2017
DOI: 10.1371/journal.pone.0177472
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-8 as an immunosuppressor in experimental autoimmune encephalomyelitis and a target of human early prognostic antibodies in multiple sclerosis

Abstract: Galectin-8 (Gal-8) is a member of a glycan-binding protein family that regulates the immune system, among other functions, and is a target of antibodies in autoimmune disorders. However, its role in multiple sclerosis (MS), an autoimmune inflammatory disease of the central nervous system (CNS), remains unknown. We study the consequences of Gal-8 silencing on lymphocyte subpopulations and the development of experimental autoimmune encephalitis (EAE), to then assess the presence and clinical meaning of anti-Gal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 87 publications
(166 reference statements)
0
38
0
Order By: Relevance
“…For CCL3 and LGALS8, lower blood levels were related with EDSS progression. In a recent study, LGALS8 was shown to have immunosuppressive protective role in CNS inflammation, by balancing the Th17 and Th1 cells . Moreover, LGALS8 was shown to be present in CSF of MS patients, and RRMS patients with antibodies against LGALS8 showed EDSS progression and worse disease prognosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For CCL3 and LGALS8, lower blood levels were related with EDSS progression. In a recent study, LGALS8 was shown to have immunosuppressive protective role in CNS inflammation, by balancing the Th17 and Th1 cells . Moreover, LGALS8 was shown to be present in CSF of MS patients, and RRMS patients with antibodies against LGALS8 showed EDSS progression and worse disease prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, LGALS8 was shown to have immunosuppressive protective role in CNS inflammation, by balancing the Th17 and Th1 cells . Moreover, LGALS8 was shown to be present in CSF of MS patients, and RRMS patients with antibodies against LGALS8 showed EDSS progression and worse disease prognosis . Interestingly, potential imbalance in peripheral Th17 and Th1 cells has also been shown to be associated with reduced gene expression of several different cytokines and chemokines in MS patients, among which CCL3 .…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-8 that also has the tandemrepeat-type architecture exerts similar immunosuppressive responses as galectin-9 does in EAE. Fittingly, EAE is exacerbated in Lgals8 −/− mice, by modulating the balance of Th17 and Th1 cells and their Tregs [288]. This galectin induces apoptosis in Th17, but not Th1 cells, and galectin-8 administration ameliorates EAE [288].…”
Section: Reduced Alternative Macrophages Activationmentioning
confidence: 99%
“…Fittingly, EAE is exacerbated in Lgals8 −/− mice, by modulating the balance of Th17 and Th1 cells and their Tregs [288]. This galectin induces apoptosis in Th17, but not Th1 cells, and galectin-8 administration ameliorates EAE [288]. In the clinical situation, the possibility for the occurrence of auto-antibodies against galectins should be considered (see below, [289,290]).…”
Section: Reduced Alternative Macrophages Activationmentioning
confidence: 99%
See 1 more Smart Citation